Effect of Variation of Temperature Field on the Process of Thermal Consolidation of Tailings Pond “Zelazny Most” - Bartlewska-Urban Monika; Strzelecki Tomasz (Studia Geotechnica et Mechanica, 2015)
The following study presents numerical calculations for establishing an impact of temperature changes on the process of distortion of bi–phase medium. The Biot consolidation equations with Kelvin–Voigt rheological skeleton were used for that purpose. The process was exemplified by thermal consolidation of post floatation dump “–elazny Most”. We analyzed the behavior of the landfill under the action of its own weight, forces of floating filtration and temperature gradient. Values of certain effective parameters of model were obtained during laboratory tests on material obtained from the landfill. The remaining data for mediums with similar characteristics were taken from literature. The results obtained from the stress state in the landfill allow the magnitude of plasticity potential to be specified based on known strength criteria. Change in the value sign of the plasticity potential clearly testifies to the emergence of an area of plasticity of material from landfill, however, this does not indicate the loss of stability of this hydrotechnical structure.